Aspects of biosafety and biosecurity in poultry - O. M. Nesterenko (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The article is devoted to analyzing aspects of biosecurity and biosecurity in the conditions of poultry farms under different poultry-keeping schemes. Production of poultry meat in the EU countries by species is broiler meat – 84.4 %, turkeys – 12.7 %, ducklings – 2.6 %, and other types of slaughtered poultry meat – 0.3 %. Ukraine is one of the five countries in the world that are the largest exporters of poultry meat to the EU, and the volume of poultry meat exported to EU member states in 2023 amounted to 97.469 tons. Compliance with basic biological safety measures is the best way to reduce the risk of spreading infectious diseases, produce safe products, and ensure veterinary food safety. Biosecurity in poultry farming involves some fundamental methods and strategies. Biosecurity is based on two fundamental principles: preventing pathogens from entering the territory of poultry farming (external biosecurity) and their further distribution (internal biosecurity). Factors of external biosecurity are the control of the penetration of biological vectors of the causative agents of poultry infectious diseases (restriction of the entry of vehicles into the farm territory, entry of outsiders, wild animals, rodents, synanthropic birds, and insects). Control of biological vectors of introducing pathogens into the farm is carried out through physical protection barriers (arrangement of fences, fences, installation of protective nets and screens on windows, doors, and ventilation shafts). The factors of internal biosecurity of poultry farms include the system of keeping poultry, proper practice of waste management (timely removal of poultry carcasses, litter, manure, method of waste management), use of hygienic means of bioprotection by employees, hygienic processing between «clean» and "dirty" areas of maintenance facilities, control and management of feed and water, cleaning and disinfection of production facilities. The level of biosecurity depends on the epizootic situation and the industry's provision of modern means of diagnosis, prevention, and treatment. In the conditions of martial law in our country, the principal risks of biological decline are the destruction of homesteads of the population and industrial-type poultry farms; the difficulty of disposing of poultry carcasses, waste from the poultry industry, and household waste following current requirements, as well as changes in the migration routes of synanthropic birds.